Analisis Tingkat Kepercayaan Masyarakat terhadap Kinerja Polri Tahun 2022: Analisis Tingkat Kepercayaan Masyarakat terhadap Kinerja Polri Tahun 2022 - Saputra, Azis; Bahari Surachman, Andika (Jurnal Litbang Polri, 2023)
This research on the level of public trust in Polri's performance in 2022 aims to measure the extent of public trust in Polri's performance in the field of police operational functions, namely Binmas, Intelligence, Traffic, Criminal Investigation and Sabhara. This research uses a mixed method which is a combination of quantitative and qualitative. The quantitative method used is a survey with a total of 50,435 respondents spread across 185 Polres in 34 Polda with a tolerance margin of error of 5%. The qualitative methods used are Focus Group Discussion (FGD) and in-depth interviews. The results of this study indicate that the value of the National Police Public Trust Index (IKM) in 2022 is 85.56 in the Very Good category. IKM Polri scores for each operational function, namely the Binmas function, 83.33; Intelkam function 87.14; Then function 85.34; Crime function 85.76; and Sabhara function 86,23. Based on the regression results on the questionnaire data, the factors that influence the IKM Polri in each operational function are categorized into; a) superior service, b) service needs improvement, c) service needs improvement. The public's perceptions and expectations also vary which shows that the community is very enthusiastic about the service programs provided by the police, such as: the Bhabinkamtibmas approach pattern with a religious and cultural basis, improving technological facilities and infrastructure in the service sector, increasing the ability to investigate cyber crimes in the digital era , and patrols in vulnerable places. Meanwhile, the police's internal perspective has also made breakthroughs and service innovations to increase public trust, such as: optimizing the presence of the police in the neighborhood, applying technology in the field of operational services, and forming special teams for crime prevention. However, there are still obstacles for Polri personnel in providing excellent service to the community, such as the limited number of personnel, limited technological facilities and infrastructure that are not evenly distributed in the region, the lack of an orderly culture of community traffic, and the limited quality of investigator human resources. Therefore, the recommendations given are adjusted from the results of the regression test in each function, namely 1) take steps to maintain superior category services, 2) take steps to improve category services that need to be improved, and 3) take steps to steps to revitalize services that need improvement.